MENGUJI KOMPLEKSITAS âILLAH HADIS - Hudaya, Hairul (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2012)
One step of the verification of the validity of the hadith is to test the aspect of âillahwhether in sanad, content or the combination of both. âIllah is understood as a form ofhidden defects in the hadith. It distinguishes between muâallal hadith and other weakhadith. The hadith scholars acknowledge that the research of âIllah aspect is one of themost difficult to test the validity of the hadith. To determine the complexity of âillahstudies, it is needed to review of the content and the chain of transmission of hadithwhich contained an âillah by the hadith scholars. The result proved that the proof ofâillah of a hadith was not easy. Hadith is born valid but apparently assessed withillah.